Understanding drugs - Gilles, Renae (21st century skills library. Upfront health., 2020)
Explores the dangerous health detriments of illicit drug use, discussing how the brain's release of dopamine can cause people, especially adolescents, to become addicted to drugs. Offers advice on making healthy choices and seeking help for addictions. Includes photographs, a glossary, an index, and resources for further research.